HnRNPM deficiency leads to cognitive deficits via disrupting synaptic plasticity. (23rd April 2021) - Akinyemi, Akinsola Raphael; Li, Dingfeng; Zhang, Juan; Liu, Qiang
Highlights: hnRNPM levels are decreased in the hippocampus of aged mice. Loss of hnRNPM in the hippocampus leads to cognitive deficit. hnRNPM deficiency reduces dendritic spine density. hnRNPM binds to the 3′UTR of synaptophysin and PSD95 mRNA and regulates their stability. Abstract: RNA metabolism involves complex and regulated processes, some of which include transcription, intracellular transport, translation, and degradation. The involvement of RNA binding proteins in these processes remains mostly uncharacterized regarding brain functions, especially cognition. In this study, we report that knockdown of hnRNPM in the CA1 hippocampal region of the mouse brain leads to learning and memory impairment. This finding is further supported, by the reduction of pre- and post-synaptic protein levels synaptophysin and PSD95. Notably, loss of hnRNPM affects the physiological spine in vivo by impairing the morphology of the dendritic spines. Additionally, our study demonstrates that hnRNPM directly binds to the 3'UTR of synaptophysin and PSD95 mRNAs, resulting in the stabilization of these mRNAs. Together, these findings present novel insight into the regulatory role of hnRNPM in neuronal structure and function.